Integrative approach in teaching primary school pupils a foreign language - Natalia V. Startseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article highlights means of increasing efficiency of teaching primary school pupils a foreign language. In our opinion, one of such means is integrative approach. Integrative approach in teaching is a specific form for providing comprehensiveness, knowledge integrity, a mean of formation of systemic thinking and scientific worldview. Means of implying integrative approach in modern training materials used in primary school classes are analyzed in the article. School subjects that can be integrated with foreign language are discovered. Integrative oriented tasks application at foreign language classes makes the process of learning and teaching not only more effective but it increases pupils’ motivation to learning in general.